Industrial Processing of Secondary Dairy Raw Materials - S.N.Obloberdiyev; M.A.Hamidova; S.U. Kuchkoraliyeva; O.B. Nurmatova; I.H. Madrimova; M.S. Tojimukhammedova (Genius Publishing Group, 2022)
A review of the most common methods of industrial processing of secondary dairy raw materials is presented. Their advantages, disadvantages and ways of optimization are indicated.
Keywords: secondary raw materials; membrane; processing; rational use